(Invited) Expectations for High-Power Semiconductors in Microwave-Assisted Chemistry. (5th January 2017) - Mitani, Tomohiko; Shinohara, Naoki
Abstract : This paper introduces availability and importance of the high-power semiconductors in the field of microwave-assisted chemistry. Microwave-assisted chemical reactions have attracted significant attention over many years, primarily because the microwave heating mechanism, so-called dielectric heating, is quite different from conventional conduction heating. Since a microwave oven was invented nearly 70 years ago, a vacuum tube device i.e. magnetron has accounted for an overwhelming share of microwave heating applications. High-power semiconductors, on the other hand, are rapidly developing throughout the 21st century. Low-cost high-power semiconductors have a great potential for future microwave heating and microwave-assisted chemistry.